Problematika Komunikasi Orang Tua dan Anak di Era Digital (Studi Fenomenologi pada Keluarga di Desa Sragi Kecamatan Talun Kabupaten Blitar) - Cici Yulianti; Sukma Ari Ragil Putri (Program Studi Komunikasi Penyiaran Islam Fakultas Dakwah dan Komunikasi, 2022)
This study was conducted to examine and analyze the problems of communication between parents and children in the digital era. This research uses a qualitative design with a phenomenological study. The concept of interpersonal communication applied by parents to children is used in discussing and reducing the communication problems that occur in it. The result of this study is that children who use gadgets experience addiction and interfere with the learning process and their growth and development. Lack of communication between parents and children is often assumed to be the cause of children breaking up and snatching murals of children who are the spearhead of a country. Another problem comes from parents, where the role of parents when the role of parents when children play with gadgets and learning is less applied.